Motion-onset VEPs reflect long maturation and early aging of visual motion-processing system - Langrová, J; Kuba, M; Kremlácek, J; Kubová, Z; Vít, F (Vision research, 2006)
Pattern-reversal and motion-onset visual evoked potentials (VEPs) were simultaneously tested in a group of 70 healthy subjects between the ages of 6-60 years to verify suspected differences in maturation and aging dynamics of the pattern and motion processing subsystems of the visual pathway. The motion-onset VEPs displayed dramatic configuration development and shortening of latencies up to 18 years of age (correl. coeff. -0.85; p < 0.001) and systematic prolongation from about 20 years of age (correl. coeff. 0.70; p < 0.001). This confirms long-lasting maturation of the magnocellular system and/or motion processing cortex and their early age related changes. Less significant changes of pattern-reversal VEPs in the tested age range can be interpreted as a sign of early maturation of the parvocellular system and its enhanced functional endurance in the elderly.
Keywords: lidé; mladiství; reakční čas; Adult; Middle Aged; zrakové dráhy; vnímání pohybu; stárnutí; Female; Visual Pathways; dítě; Adolescent; Humans; Motion Perception; Reaction Time; Photic Stimulation; světelná stimulace; lidé středního věku; Evoked Potentials, Visual; mužské pohlaví; ženské pohlaví; Aging; Male; zrakové evokované potenciály; Child; dospělí